Comorbidities in transplant recipients with acute myeloid leukemia receiving low-intensity conditioning regimens: an ALWP EBMT study - Fein Joshua A.; Shouval Roni; Galimard Jacques-Emmanuel; Labopin Myriam; Socié Gérard; Finke Jürgen; Cornelissen Jan J.; Malladi Ram; Itälä-Remes Maija; Chevallier Patrice; Orchard Kim H.; Bunjes Donald; et al. (ELSEVIER, 2026)
Older age and a high burden of comorbidities often drive the selection of low-intensity conditioning regimens in allogeneic hematopoietic stem cell transplantation recipients. However, the impact of comorbidities in the low-intensity conditioning setting is unclear. We sought to determine the contribution of individual comorbidities and their cumulative burden on the risk of nonrelapse mortality (NRM) among patients receiving low-intensity regimens. In a retrospective analysis of adults (>= 18 years) who underwent transplantation for acute myeloid leukemia in the first complete remission between 2008 and 2018, we studied recipients of low-intensity regimens as defined by the transplantation conditioning intensity (TCI) scale. Multivariable Cox models were constructed to study associations of comorbidities with NRM. Comorbidities identified as putative risk factors in the low-TCI setting were included in combined multivariable regression models assessed for overall survival, NRM, and relapse. A total of 1663 patients with a median age of 61 years received low-TCI regimens. Cardiac comorbidity (including arrhythmia/valvular disease) and psychiatric disease were associated with increased NRM risk (hazard ratio [HR], 1.54; 95% confidence interval [CI], 1.13-2.09 and HR, 1.69; 95% CI, 1.02-2.82, respectively). Moderate pulmonary dysfunction, though prevalent, was not associated with increased NRM. In a combined model, cardiac, psychiatric, renal, and inflammatory bowel diseases were independently associated with adverse transplantation outcomes. These findings may inform patient and regimen selection and reinforce the need for further investigation of cardioprotective transplantation approaches.